OPTIMALISASI PRODUK DAN PEMASARAN UMKM PENGRAJIN KURSI BAMBU HITAM (KUBU-TAM) DESA SIMPANG MBACANG - Alfis Arif; Debi Gusmaliza; Elpita Aisyah (LPPM Universitas Bina Bangsa, 2023)
The aim of this service is to optimize the products and marketing of MSME black bamboo chair craftsmen (Kubu-Tam) in Simpang Mbacang Village. UMKM Kubu-Tam Simpang Mbacang in carrying out the production process still uses manual tools and the sales process is still conventional and there is no financial recording system. This affects the amount of production and marketing which is not optimal which results in not maximal income. So, in this service, education and application will be carried out regarding the use of electrical production tools/machines, creating social media and e-commerce for digital marketing and financial recording systems. The method used is the DMAIC method and the realization is carried out through lectures and direct practice. The evaluation method used is pretest and post-test. The results of the service show that production equipment is electrical/machined, sales are using social media, e-commerce and there is a financial management system for MSMEs. And the results of the pretest and posttest showed an increase in participants' understanding from 40% to 90%. This means that community service activities were successful